Preclinical Evaluation of Efficacy and Safety of an Improved Lentiviral Vector for the Treatment of β-Thalassemia and Sickle Cell Disease - Negre, Olivier; Bartholomae, Cynthia; Beuzard, Yves; Cavazzana, Marina; Christiansen, Lauryn; Courne, Celine; Deichmann, Annette; Denaro, Maria; de Dreuzy, Edouard; Finer, Mitchell; Fronza, Raffaele; Gillet-Legrand, Beatrix; et al. (Current Gene Therapy, 2015)
A previously published clinical trial demonstrated the benefit of autologous CD34+ cells transduced with a selfinactivating lentiviral vector (HPV569) containing an engineered β-globin gene (βA-T87Q-globin) in a subject with β thalassemia major. This vector has been modified to increase transduction efficacy without compromising safety. In vitro analyses indicated that the changes resulted in both increased vector titers (3 to 4 fold) and increased transduction efficacy (2 to 3 fold). An in vivo study in which 58 β-thalassemic mice were transplanted with vector- or mock-transduced syngenic bone marrow cells indicated sustained therapeutic efficacy. Secondary transplantations involving 108 recipients were performed to evaluate long-term safety. The six month study showed no hematological or biochemical toxicity. Integration site (IS) profile revealed an oligo/polyclonal hematopoietic reconstitution in the primary transplants and reduced clonality in secondary transplants. Tumor cells were detected in the secondary transplant mice in all treatment groups (including the control group), without statistical differences in the tumor incidence. Immunohistochemistry and quantitative PCR demonstrated that tumor cells were not derived from transduced donor cells. This comprehensive efficacy and safety data provided the basis for initiating two clinical trials with this second generation vector (BB305) in Europe and in the USA in patients with β-thalassemia major and sickle cell disease.
Keywords: β-hemoglobinopathy